Altered Bone Metabolism and Bone Density in Patients with Chronic Pancreatitis and Pancreatic Exocrine Insufficiency - Haas, Stephan; Krins, Stefan; Knauerhase, Andreas; Löhr, Matthias (JOP. Journal of the Pancreas, 2015)
Context Due to maldigestion, pancreatic exocrine insufficiency (PEI) in chronic pancreatitis may lead to deficiencies in fat-soluble vitamins, including vitamin D. This may, in turn, can cause disturbances in bone metabolism and reduce bone mineral density. Objective To conduct a prospective study of maldigestion, bone metabolism, and bone mineral density in a group of patients with chronic pancreatitis. Methods A total of 50 male patients with proven chronic pancreatitis (36/50 alcohol; 42/50 smokers) were studied. Pancreatic exocrine function was assessed using the fecal elastase-1 test. Blood and urine samples were analyzed for parameters related to pancreatitis, nutrition, endocrine status, and bone metabolism. Bone mineral density was measured with dual-energy X-ray absorption (DXA) and conventional vertebral X-rays. A standardized questionnaire for osteoporosis was given. Results Twenty-eight of the patients had PEI (fecal elastase-1 <200 µg/g), 25 had bone pain, and 21 had a history of bone fractures. Serum 25-OH-cholecalciferol and urine calcium were decreased and deoxypyridinoline concentrations were increased in urine. Serum calcium, bone-specific alkaline phosphatase, and parathyroid hormone were within normal limits. There was no statistical correlation between three classes of fecal elastase-1 (<100 µg/g; 100-200 µg/g; >200 µg/g) and calcium, 25-OH-cholecalciferol, or deoxypyridinoline. Of the 15 patients who underwent DXA, 5 had normal bone mineral density (T score >-1), 9 had osteopenia (T score from -1 to – 2.5), and 1 had osteoporosis (T score <-2.5). There was a trend toward a correlation between low fecal elastase-1 and low T scores (P=0.065). Low fecal elastase-1 correlated with low bone mineral density in conventional X-rays (P<0.05). Patients receiving pancreatic enzyme replacement therapy (PERT) had significantly higher DXA values (P<0.05). Conclusions Patients with chronic pancreatitis have osteoporosis, along with abnormal bone metabolism and reduced bone mineral density as measured by DXA and X-ray. PERT is associated with less osteopathy. Image: Bone mineral density in correlation with fecal elastase-1.